Educational Tourism-Based Digital Learning Management Model for Sustainable Human Capital Development in Coastal Areas - Naufal Ramadian; Dede Latipah; Muhamad Alimudin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to develop and validate an Educational Tourism-Based Digital Learning Management Model for Sustainable Human Capital Development in Coastal Areas. The research addresses the challenge of aligning digital transformation in education with local economic characteristics in coastal regions where tourism plays a dominant role. A Research and Development (R&D) approach was employed, involving needs assessment, model design, expert validation, limited field testing, and evaluation. The study was conducted in a coastal senior high school with 139 student participants and 15 teachers selected through proportional and purposive sampling techniques. Data were collected using validated questionnaires, interviews, and observations, and analyzed through descriptive statistics and multiple regression analysis. The findings indicate that digital learning management and educational tourism integration significantly contribute to human capital development, explaining 41.5% of its variance. Educational tourism integration demonstrated a stronger predictive effect compared to digital management alone. The implementation process also fostered improved teacher collaboration, increased student engagement, and strengthened school–community partnerships. These results suggest that integrating contextual tourism-based learning within digital management systems enhances the relevance and sustainability of education in coastal environments. The study provides a practical model that can support regional development strategies by connecting formal education with local economic ecosystems.